Pelatihan Penjadwalan Proyek Konstruksi Dengan Aplikasi Microsoft Project Pada Siswa SMKN 5 Surabaya - Gde Agus Yudha Prawira Adistana; Meity Wulandari; Purwo Mahardi; Muhammad Imaduddin; Mochamad Firmansyah Sofianto; Lynda Refnitasari (Kanigara, 2022)
Learning related to scheduling is done manually and with the help of Microsoft Excel applications. In its implementation, there are still some minor errors that cause changes in the total cost as a whole. The use of applications such as Microsoft Project is believed to be able to minimize the occurrence of this error because of the workflow control feature. The implementation of community service is expected to be able to increase knowledge and improve students' skills in preparing schedules appropriately and in accordance with applicable rules. From the questionnaire, it can be concluded that the students felt this training helped them to be more familiar with the scheduling function with Microsoft Project and helped to better understand the Construction Cost Estimation (EBK) learning.